Manajemen Desain Lingkungan Pendidikan Anak Usia Dini - Tresa Nur Anggreani; Hadisa Putri (CV Putra Publisher, 2025)
Early Childhood Education (ECED) is the most important stage of a child's development, as it is during this time that the basic foundations for cognitive, emotional, social and physical development are built. Environmental design in early childhood education plays a crucial role in supporting children's learning and development. An effective environmental design not only prioritizes visual aesthetics, but also considers various important aspects such as safety, hygiene, comfort, as well as the principles of environment-based education. Good design management in ECD requires a holistic approach that integrates children's physical, psychological and social needs. Therefore, it is important to create an environment that is not only safe and comfortable, but also supports creativity, social interaction, and stimulates children's curiosity. This research aims to explore how environmental design principles can be effectively applied in an ECD context, as well as to identify factors that influence the quality of learning environments for young children. By creating a pleasant and productive environment, it is hoped that children can learn to their full potential and develop their potential optimally.